A gamification tool in teaching and learning / Norul Fadhilah Ismail and Mahfuzah Mahayadin - Ismail, Norul Fadhilah; Mahayadin, Mahfuzah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Gamification in education has gained significant traction as a strategy to enhance student engagement, motivation, and learning outcomes due to the development of digital technology and mobile applications. The term “gamification of education” refers to a growing strategy for raising students’ motivation and engagement by introducing game design features in classroom settings (Dichev & Dcheva, 2017). Incorporating game elements and learning activities into gamified learning can heighten students' inherent motivation, transforming educational tasks into enjoyable and fulfilling experiences (Koivisto & Hamari, 2019). Apart from that, gamification can boost cognitive load and achievement levels, and students generally have positive thoughts regarding gamification strategies. However, when gamification is applied, the cognitive load factor must be considered, and certain precautions must be taken to maximise effectiveness. (Turan et al., 2016).